Diferensiasi Public Speaking Online di Era Digitalisasi Pasca Pandemi Covid -19: Studi Kasus Mengenai Diferensiasi Public Speaking Online Di Era Digitalisasi Pasca Pandemi Covid-19 pada Kalangan Dosen di Kota Bandung - Rizki Surya Tawaqal; Maudy Rizkiana Poedjadi; Amy Elva Silviany (MUKASI: Jurnal Ilmu Komunikasi, 2024)
The digitalization era post-Covid-19 pandemic has brought significant changes in various aspects of life, including Public Speaking techniques. This study aims to explore the differences in Public Speaking techniques before and after the pandemic and how adaptation to digital platforms affects communication effectiveness. Before the pandemic, Public Speaking was often conducted face-to-face, focusing on body language, eye contact, and voice intonation to capture the audience's attention. However, the pandemic forced many Public Speaking activities to shift to digital platforms. This shift requires speakers to master technology, understand the dynamics of virtual interaction, and adapt their presentation techniques to remain interactive. This study uses qualitative methods by collecting data through in-depth interviews with Public Speaking practitioners and related literature analysis. The findings show that successful speakers in this digital era are those who can effectively utilize technology, use attractive visual aids, and develop adaptive communication skills. Additionally, factors such as time management, maintaining audience engagement through interactive features, and understanding digital communication ethics are key to success. The conclusion of this study emphasizes the importance of continuous training and adaptation for public speakers to remain relevant and effective in the digitalization era. Furthermore, there is a need for developing curricula and training programs that support the mastery of new techniques in Public Speaking. Thus, this change not only presents challenges but also opportunities to enhance the overall quality of public communication